Building a community-driven bioinformatics platform to facilitate Cannabis sativa multi-omics research - Mansueto, Locedie; Kretzschmar, Tobias; Mauleon, Ramil; King, Graham J. (GigaByte (Hong Kong, China), 2024)
Global changes in cannabis legislation after decades of stringent regulation and heightened demand for its industrial and medicinal applications have spurred recent genetic and genomics research. An international research community emerged and identified the need for a web portal to host cannabis-specific datasets that seamlessly integrates multiple data sources and serves omics-type analyses, fostering information sharing. The Tripal platform was used to host public genome assemblies, gene annotations, quantitative trait loci and genetic maps, gene and protein expression data, metabolic profiles and their sample attributes. Single nucleotide polymorphisms were called using public resequencing datasets on three genomes. Additional applications, such as SNP-Seek and MapManJS, were embedded into Tripal. A multi-omics data integration web-service Application Programming Interface (API), developed on top of existing Tripal modules, returns generic tables of samples, properties and values. Use cases demonstrate the API’s utility for various omics analyses, enabling researchers to perform multi-omics analyses efficiently. Availability and implementation The web portal can be accessed at www.icgrc.info.